2021
DOI: 10.1007/s40544-021-0526-0
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of several surface treatment processes for alleviating fretting damage of a locking pin

Abstract: The operational safety and reliability of a variable gauge train are affected by the anti-fretting wear performance of the locking mechanism. The main purpose of this study is to optimize the surface treatment process for a locking pin material under actual service conditions to alleviate fretting damage. Based on the two basic principles of surface strengthening and friction reduction, a substrate (AISI 4135 steel) surface was treated by laser quenching (LQ), plasma nitriding (PN), and bonded MoS2 coating. Sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Under the action of external loads, the debris on the compacted surface migrates reciprocally. In addition, the dry sliding process is accompanied by frictional heat and air, and oxidation of the debris occurs, which eventually leads to third-body wear [49,50]. Figure 12 shows the fretting wear morphologies and EDS results of the TiAlN coatings.…”
Section: In Dry Slidingmentioning
confidence: 99%
“…Under the action of external loads, the debris on the compacted surface migrates reciprocally. In addition, the dry sliding process is accompanied by frictional heat and air, and oxidation of the debris occurs, which eventually leads to third-body wear [49,50]. Figure 12 shows the fretting wear morphologies and EDS results of the TiAlN coatings.…”
Section: In Dry Slidingmentioning
confidence: 99%
“…27 Because of its excellent properties, such as exhibiting low shear resistance, promoting interlayer slip, and reducing interfacial friction, it is among the excellent candidates for liquid lubrication of mechanical moving parts. 28,29 By virtue of its excellent properties, scholars have been studying the potential applications of using MoS 2 as a lubricant additive and reporting breakthroughs in the field of lubrication. 30−33 Regrettably, MoS 2 also has some weaknesses, with strong van der Waals force interactions among the layers that lead to interlayer aggregation, which limits its interlayer slip, and difficulty in dispersion in the base oil, thus hindering the lubrication and wear resistance of MoS 2.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As a new nanomaterial, molybdenum disulfide (MoS 2 ) has attracted great attention since its discovery . Because of its excellent properties, such as exhibiting low shear resistance, promoting interlayer slip, and reducing interfacial friction, it is among the excellent candidates for liquid lubrication of mechanical moving parts. , By virtue of its excellent properties, scholars have been studying the potential applications of using MoS 2 as a lubricant additive and reporting breakthroughs in the field of lubrication. Regrettably, MoS 2 also has some weaknesses, with strong van der Waals force interactions among the layers that lead to interlayer aggregation, which limits its interlayer slip, and difficulty in dispersion in the base oil, thus hindering the lubrication and wear resistance of MoS 2. , To overcome the limitations of single lubricant additives in fluid lubrication, the help of dispersants, grafting of surfactants, and other techniques are the basic steps used to improve the dispersion stability of MoS 2 in a fluid medium. ,,, Correspondingly, Kumari et al introduced a method of grafting octadecyl amines at the structural defects of MoS 2 nanosheets as high-performance lubricant additives, which can make the grafting process have more affinity and fully exploit its properties in the field of lubrication.…”
Section: Introductionmentioning
confidence: 99%
“…High-strength titanium alloys are widely used for aircraft fasteners due to their strong ability to lose weight, excellent corrosion resistance, cold formability, and good compatibility with composite materials. For high-strength titanium alloy fasteners, fretting damage, as one of the common damage failure modes of aircraft fasteners, is the key factor restricting their reliability and service life . According to the statistics from the United States Air Force, fretting damage accounts for over one-sixth of damage in aero-engines, especially reducing the fatigue limit to only one-third of the ordinary fatigue limit. Hence, a number of researchers have paid extensive attention to fretting damage in titanium alloys. …”
Section: Introductionmentioning
confidence: 99%
“…Most of them have devoted to conceiving the fretting behavior and revealing the interplay relationship between damage and fretting conditions. In addition to fretting conditions, material intrinsic factors also affect the sensitivity to fretting damage of alloys, such as crystallographic orientation and microstructural features. , For example, Takeda et al found that the fretting fatigue limit of Ti-4.5Al-3V-2Mo-2Fe alloy increased with a decrease in the volume fraction and the average grain size of the primary α phase. Especially, microstructural features also change the sensitivity to fretting damage by modifying the mechanical properties of materials, such as toughness, hardness and crack initiation, and propagation resistance. , In addition, the protecting effect of the tribolayer (the third body) also crucially affects the fretting damage. , However, there have been few studies on the effect of microstructural features on the fretting damage especially induced by the tribolayer evolution characteristic, which was considered to simply correlate with the surface hardness in most previous studies. For example, Sharma et al found that the formation of a mechanically mixed tribolayer consisting of (Cu,Fe,Ti) x O y and hard TiB 2 particles can effectively reduce wear, which is consistent with Archard’s law.…”
Section: Introductionmentioning
confidence: 99%